A Stock-Adjustment Investment Model - Greenberg, Edward (Econometrica, 1964)
Firms' investment in plant and equipment is explained by a stock-adjustment model in which the coefficient of adjustment is allowed to vary. It is assumed that firms partially close the gap between desired and actual capital stock, but that the speed of adjustment depends on the firm's ability to procure funds at reasonable cost. A panel of individual firm responses to the McGraw-Hill plant and equipment survey is the principal data source, supplemented by financial statement information for the firms and two indices representing costs of debt and equity financing. The predictions generated by the regressions are aggregated for comparison with the observed aggregates. 1. A STOCK-ADJUSTMENT INVESTMENT MODEL THE PURPOSE of this paper is to develop and test a model to explain firms' investment in plant and equipment. The model incorporates features which recent research on the investment decision suggests are significant. The basic framework is a stock-adjustment model, in which each year the firm moves partially toward its desired position, with the coefficient of adjustment (reaction coefficient) allowed to vary by firm and year. The model has the form